Chronopotentiometric Approach of CO2 Reduction in Molten Carbonates. Issue 8 (9th May 2017) - Meléndez-Ceballos, A.; Brouzgou, A.; Crapart, C.; Albin, V.; Lair, V.; Cassir, M.
Abstract : Carbon capture and valorization is a new route increasingly discussed to reduce greenhouse gas emissions. One of the paths foreseen for CO2 valorization is its transformation into fuels by electrochemical reduction of carbon dioxide. In this approach, molten carbonates are of particular interest since they can be used to capture CO2 molecule because of its high solubility; hence, valorization by electrolysis is possible in molten carbonate media. To better understand CO2 reduction, chronopotentiometric and chronoamperometric techniques were used at gold and graphite electrodes immersed in four alkali carbonate eutectics, Li-Na, Li-K, Li-Na-K and Na-K. The results complemented a previous work based on cyclic voltammetry and confirmed the existence of a main CO2 reduction phenomena around −1.2 V vs Ag/Ag + that involves two one-electron steps or a two-electron unique step. Transition time analysis showed that the reduction mechanism is either simultaneous reduction of CO2 adsorbed and diffusion species or rapid equilibrium between adsorbed and diffusing species. Furthermore, we identified another electrochemical system involving adsorbed CO2 and CO at higher potentials. In summary, we have succeeded in proving and précising some previous results, as well as identifying reduction mechanisms.